Melas, Stroke-Like Episodes and Ketogenic Diet - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at University of Toronto and McMaster University, Canada, report a 22-year-old woman with multiple episodes of status epilepticus and migratory cortical stroke-like lesions.